Bardet-Biedl Syndrome: a case report of delayed diagnosis with variable presentation and role of genetic testing in definitive diagnosis - Gargi Ramesh Rekhawar; M. P. Bhavana; Vishal Dnyaneshwar Sawant; Sushma Save; Alpana Kondekar (SpringerOpen, 2023)
Abstract Background Bardet-Biedl syndrome (BBS) is a rare multisystemic autosomal recessive (AR) disorder, which falls under the spectrum of ciliopathic disorders. As BBS is a very rare entity in India, its diagnosis is most often missed during early child visits. The lack of a syndromic approach for diagnosing genetic disorders by health care physicians is being considered a major blackguard. The following case report exemplifies how a patient presenting with multisystemic involvement should be evaluated to rule out syndromic association. Case presentation The authors here report a case of a male child aged 13 years presenting to Pediatrics Outpatient with complaints of learning disability and behavioral disturbances. During his initial assessment, features such as polydactyly, overweight, and vision disturbances were picked up by the pediatrician as an indication towards syndromic association. Soon a complete laboratory workup and various scans were done which revealed hepatic fibrosis and gonadal dysgenesis. Simultaneously, IQ testing was recommended which was suggestive of mild mental retardation. Bringing along all these clinical presentations a diagnosis of BBS was made. Post-diagnosis parents were counseled on recurrence risk and explained the importance of regular follow-ups and screening to improve quality of life. Conclusion This case report emphasizes the role of holistic multidisciplinary approach for diagnosing at early stage and better prognosis of BBS. Prenatal genetic counseling along with next-generation sequencing are a few potential measures to drop the incidence of this condition. Obesity and visual disturbances are a few concerns which if not handled early can result in unfortunate outcomes. Renal involvement in BBS is considered a deadly parameter which surely was not seen in this case. For all learning/intellectual disabilities, the triad of screening, clinical examination, and interdisciplinary approach can clinch in early diagnosis of a genetic syndrome.